Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd009437
|View full text |Cite
|
Sign up to set email alerts
|

Integrated disease management interventions for patients with chronic obstructive pulmonary disease

Abstract: Chavannes, N. H. (2013). Integrated disease management interventions for patients with chronic obstructive pulmonary disease. Cochrane Database of Systematic Reviews, (10), [009437].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
2
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(171 citation statements)
references
References 60 publications
3
153
2
13
Order By: Relevance
“…Evidence supporting specific system-level interventions for nodule evaluation is limited, but these have been shown to be helpful in other settings (75)(76)(77). Possible interventions could include: creation of multidisciplinary teams, standardized reporting of results, development of care pathways, and development of registries to track patients with nodules.…”
Section: Logistics and Implementationmentioning
confidence: 99%
“…Evidence supporting specific system-level interventions for nodule evaluation is limited, but these have been shown to be helpful in other settings (75)(76)(77). Possible interventions could include: creation of multidisciplinary teams, standardized reporting of results, development of care pathways, and development of registries to track patients with nodules.…”
Section: Logistics and Implementationmentioning
confidence: 99%
“…These interventions, including nurse-administered home care for AECOPD,8–10 disease-specific self-management plans,11 12 implementation of the chronic care model,13 and home visits by respiratory health workers,14–16 have had variable degrees of success. A recent meta-analysis of 26 trials with different programme designs in various healthcare settings, and with a follow-up period of between 3 and 24 months, has suggested that integrated disease-management programmes improved disease-specific QOL and exercise capacity, in addition to reducing hospital admissions and hospital days per person 17. To the best of our knowledge, there has been no randomised controlled trial (RCT) that specifically evaluates the effects of a comprehensive programme with multidisciplinary input on patients who have just been discharged from hospital after treatment of AECOPD, although there are data suggesting that a post-AECOPD rehabilitation programme and self-management can help to decrease exacerbations and improve the QOL of such patients 18 19.…”
Section: Introductionmentioning
confidence: 99%
“…21 The lack of impact on COPD emergency department visits may be due to the emergency department functioning as an out-patient or rescue clinic for patients with exacerbations of their disease. 22,23 The reduction in ICU and hospital days for COPD readmissions in the intervention arm may be due to subjects coming into the hospital earlier or possibly receiving 24 found that these programs improved the quality of life of subjects with COPD, improved exercise performance, and reduced hospital admissions as well as the number of hospital days per person. Similarly, Zwerink et al 25 reported that selfmanagement interventions in subjects with COPD were associated with improved health-related quality of life, a reduction in respiratory-related hospital admissions, and improvement in dyspnea.…”
Section: Discussionmentioning
confidence: 99%